Lies Noorlita Elvandari, 2017 STUDENTS' EXTRADIEGETIC AND DIEGETIC EMOTIONS WHEN READING SELECTED PICTUREBOOK: A COGNITIVE CRITICISM universitas Pendidikan Indonesia | repository.upi.edu | perpustakaan.upi.edu - Lies Noorlita Elvandari, - (2017)
This paper takes as its point of departure cognitive criticism, the direction of inquiry that investigates readers' cognitive and affective engagement with literature, partly based on recent brain research. This research was intended to find out students' extradiegetic and diegetic emotions when reading Where the Wild Things Are by Maurice Sendak (1963). The research was conducted in a high school in Bandung with 31 students involved as the participants. The research employed a qualitative research design in which the data were collected through written responses and interview. The research found that there were six extradiegetic emotions, namely: serenity, fear, admiration, disappointment, apathy, and boredom. In addition, this study categorizes the diegetic emotions into two types of emotions: basic and social emotions. Basic emotions emerged when students read selected picturebook were anger, fear, and happiness. Meanwhile, what includes in social emotions were love, contentment, pride and guilt. The ultimate argument of the paper is that fiction provides an excellent training field for young readers' developing of theory of mind and empathy skills. ---Skripsi ini berangkat dari teori cognitive criticism dengan tujuan untuk menginvestigasi keterlibatan siswa dengan karya sastra secara kongnitif dan afektif, yang didasarkan oleh penelitian yang dilakukan pada otak manusia. Penelitian ini bertujuan untuk menemukan emosi extradiegetic dan diegetic ketika siswa membaca karya sastra berjudul Where the Wild Things Are oleh Maurice Sendak (1963). Penelitian diadakan di sebuah sekolah menengah atas di Bandung dengan melibatkan 31 siswa sebagai partisipan. Penelitian ini menggunakan desain penelitian kualitatif yang mana data-datanya dikumpulkan dari respon tertulis dan interview. Terdapat enam emosi extradiegetic yang ditemukan pada penelitian ini, yaitu: ketentraman, ketakutan, kekaguman, kekecewaan, keapatisan, dan kebosanan. Penelitian ini mengkategorikan emosi diegetic menjadi dua bagian, yang pertama adalah emosi dasar dan yang ke dua adalah emosi social. Emosi dasar yang muncul ketika siswa membaca Where the Wild Things Are adalah kemarahan, ketakutan, dan kebahagiaan. Selain itu, yang termasuk ke dalam emosi sosial adalah cinta, kepuasan, rasa bangga, dan rasa bersalah. Argumen utama dari penelitian ini adalah bahwa fiksi memberikan kesempatan unggul dalam melatih dan mengembangkan kemampuan theory of mind dan empati siswa